Web Developer.com Guide to Search Engines - Sonnenreich, Wes and Macinta, Tim, 1975- (New York J. Wiley, 1998)
Web Developer.com Guide to Search Engines is a complete guide to choosing, obtaining, installing, configuring, supporting, and building the perfect search engine for your website, intranet, enterprise network, or Internet needs. Wes Sonnenreich and Tim Macinta, two former members of the MIT Media Lab, critically appraise the leading search engines, explaining who built them, how they work, and the relative advantages and disadvantages of each. Plus, they tell you everything you need to know in order to determine your ideal search parameters and create a profile of your site; match your site profile with the best engine for the job; obtain, install, configure, maintain, and get help for each engine; and build your own custom search engine from scratch.
Include Index and Illustration
Keywords: Database searching--Computer programs